Coagulation status and determinants of possible aspirin resistance in patients with essential thrombocythemia - Yang, Erpeng; Lv, Yan; Wang, Ziqing; Wang, Dehao; Li, Yumeng; Sun, Yan; Zhang, Yanyu; Niu, Jicong; Chen, Zhuo; Liu, Weiyi; Hu, Xiaomei (Frontiers in Medicine, 2022)
Objectives: The currently recommended aspirin regimen appears inadequate for thromboprophylaxis in essential thrombocythemia (ET). This study aimed not only to evaluate the curative effect of aspirin but also to explore the coagulation status and determinants of aspirin resistance (AR) of ET patients. Methods: A total of 80 ET patients who underwent coagulation tests, thromboelastography (TEG), and next-generation sequencing (NGS) were involved in the study. Patients were divided into the aspirin sensitivity (AS) group and AR group according to the arachidonic acid inhibition rate. Their clinical features and coagulation function were analyzed. Results: The incidence of AR was 53.75% (43/80) in 80 ET patients. Fbg was significantly higher in coagulation tests in AR patients compared with AS patients (P < 0.05), while the differences in other variables (D-D, PT, PTA, INR, APTT, TT, FDP, AT-III) were not statistically significant (P > 0.05). Compared with AS patients, the K values, α angles, MA values, and CI values of TEG in AR patients were statistically smaller (P < 0.05), but there was no significant difference in R value between them (P > 0.05). Univariate and multivariate logistic regression analysis showed that age, irregular use of aspirin, smoking, dyslipidemia, and hypertension increased the risk of AR (P < 0.05). In the routine NGS, the driver gene and non-driver gene had no effect on aspirin resistance in ET patients. Conclusion: Compared with AS patients, AR patients have enhanced platelet aggregation function, are in a relatively hypercoagulable state, and have elevated fibrinogen function/levels, all of which cause a worse coagulation status. ET patients with increasing age, irregular use of aspirin, smoking, dyslipidemia, and hypertension are possibly at higher risk of AR. The routine NGS may not be helpful for the prediction of AR, therefore we recommend adding relevant drug-resistance genes to NGS.